Undang-Undang PKDRT dalam Perspektif Hadis - Khairuddin, Ahmad (Jurnal Muadalah, 2013)
To protect family members from violence, in particular the government has adopted the Law on the Elimination of Domestic Violence (PKDRT) in 2004. In the Act, violence includes four types: physical, psychological, economic and sexual violences. Islamic teachings, especially those derived from the hadith, contain a number of provisions which also provide protection for family members, particularly wives, as mentioned in the Domestic Violence Act. Prophet, for example, denounced those who hit wife like beating slaves, prohibited the insult of wife, gave economic rights and prohibited the prostitution of female slaves. However, not all categories of violence that exist in PKDRT are shared by the tradition. There is a difference between the two, especially in relation to sexual violence against wives.